The origins, history, and future of the Federal Reserve : a return to Jekyll Island - Bordo, Michael D.; Roberds, William. (Studies in macroeconomic history, 2013)
"This book contains essays presented at a conference held in November 2010 to mark the centenary of the famous 1910 Jekyll Island meeting of leading American financiers and the U.S. Treasury. The 1910 meeting resulted in the Aldrich Plan, a precursor to the Federal Reserve Act that was enacted by Congress in 1913. The 2010 conference, sponsored by the Federal Reserve Bank of Atlanta and Rutgers University, featured assessments of the Fed's near 100-year track record by prominent economic historians and macroeconomists. The final chapter of the book records a panel discussion of Fed policy making by the current and former senior Federal Reserve officials. ch1: "To Establish a More Effective Supervision of Banking:" How the Birth of the Fed Altered Bank Supervision Abstract Although bank supervision under the National Banking System exercised a light hand and panics were frequent, depositor losses were minimal. Double liability induced shareholders to carefully monitor bank managers and voluntarily liquidate banks early if they appeared to be in trouble. Inducing more disclosure, marking assets to market, and ensuring prompt closure of insolvent national banks, the Comptroller of the Currency reinforced market discipline. The arrival of the Federal Reserve weakened this regime. Monetary policy decisions conflicted with the goal of financial stability and created moral hazard. The appearance of the Fed as an additional supervisor led to more "competition in laxity" among regulators and "regulatory arbitrage" by banks. When the Great Depression hit, policy-induced deflation and asset price volatility were misdiagnosed as failures of competition and market valuation. In response, the New Deal shifted to a regime of discretion-based supervision with forbearance"--